Variation in seed yield and morphological traits in Turkish grass pea (Lathyrus sativus) genotypes - Basaran U.; Mut H.; Onal Asci O.; Gulumser E.; Acar Z.; Ayan I. (New approaches for grassland research in a context of climate and socio-economic changes, 2012)
In this study 51Turkish landraces, 4 ICARDA lines and 1 registered variety of Lathyrus sativus L. were investigated for morphological characters and seed yield. The experiment was carried out in Samsun ecological conditions in 2009 with spring-sown. A high variation was determined among genotypes regarding the investigated characters, especially in seed yield and thousand seed weight. The variation among the Lathyrus sativus genotypes was between 2.82 g/plant and 13.64 g/plant for seed yield and between 5.10 g/plant and 22.89 g/plant for biological yield and between 91.65 g and 167.70 g for thousand seed weight. Many of the landraces had higher seed yield and thousand seed weight than registered cultivar named “Gurbuz 2001”. Correlation analysis showed that biological yield, stem number, pod number per plant and petiole length highly and positively correlated with seed yield.
14. Meeting of the FAO-CIHEAM Subnetwork on Mediterranean Forages and Fodder Crops, 2012/10/03-06, Samsun (Turkey)